2012
DOI: 10.1177/1753193412453664
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthesia versus intravenous regional anaesthesia in endoscopic carpal tunnel release: a randomized controlled trial

Abstract: We carried out a prospective randomized trial in 38 patients to compare intravenous regional anaesthesia with local anaesthesia in endoscopic carpal tunnel release using the Agee single-portal technique. There was no significant difference in reported pain during surgery. Immediately after surgery, patients in the local anaesthesia group reported significantly less pain in the hand and at the tourniquet. Two hours after surgery, patients in the local anaesthesia group reported significantly less hand pain. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…This difference has been mainly attributed to the additional volume of instruments under the intact flexor retinaculum that might cause pressure on the nerve. Nabhan et al [13] and Sorensen et al [14] infiltrated the subcutaneous area of palmar proximal wrist as well as the distal wrist down to the palm before endoscopic surgery. In both studies, no significant problems with visibility during endoscopic division of the transverse carpal ligament were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference has been mainly attributed to the additional volume of instruments under the intact flexor retinaculum that might cause pressure on the nerve. Nabhan et al [13] and Sorensen et al [14] infiltrated the subcutaneous area of palmar proximal wrist as well as the distal wrist down to the palm before endoscopic surgery. In both studies, no significant problems with visibility during endoscopic division of the transverse carpal ligament were reported.…”
Section: Discussionmentioning
confidence: 99%
“…There were no complications related to the endoscopic surgery and the hand functional outcome was equal in both groups during follow up examination. In another prospective randomised trial, Sorensen et al [14] compared intravenous regional anaesthesia with local anaesthesia in endoscopic carpal tunnel release using the Agee singleportal technique. There was no significant difference in reported pain during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…37 A third trial provided level II evidence that local anesthesia reduces postoperative pain in endoscopic carpal tunnel release compared with intravenous regional anesthesia. 38 All 3 of the above studies also pointed out that endoscopic carpal tunnel can be easily performed with local anesthetic infiltration into the operative site.…”
Section: Local Anesthesia For Endoscopic Carpal Tunnel Releasementioning
confidence: 98%
“…This study was conducted at Rothman Institute, Thomas Jefferson University, Philadelphia, Pennsylvania. All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2008 (5). Informed consent was obtained from all patients for being included in the study.…”
Section: Notementioning
confidence: 99%
“…These efforts have included utilizing less invasive surgical techniques, moving the surgeries to outpatient facilities 1 and using portable hand tables to improve turnover time and efficiency, eliminating postoperative physical therapy 2 and postoperative splinting, 3 and simplifying perioperative anesthesia. 4,5 A 2015 study polled members of the American Society of Surgeons of the Hand and found that 43% of respondents use intravenous sedation during CTR, whereas 8% perform the surgery with local anesthesia alone leaving the patient wide awake. 6 The "wide-awake local anesthesia with no tourniquet" (WALANT) anesthesia technique has gained attention in recent years due to its convenience, cost-effectiveness, [7][8][9] and high level of patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%